Pengaruh Servicescape dan Menu Diversity terhadap Kepuasan Pelanggan dan Dampaknya terhadap Loyalitas Pelanggan - Yuana Putri, Mita Septiana; Huda, Miftahul (Economic Reviews Journal, 2024)
This study aims to determine and measure the influence of Servicescape and Menu Diversity on Customer Satisfaction and Customer Loyalty in Prigen District. This study is a quantitative study with a sample of 116 respondents using purposive sampling techniques with SPSS 22 analysis tools. The results of the study indicate that Servicescape has a significant effect on Customer Satisfaction, Menu Diversity has a significant effect on Customer Satisfaction, Servicescape has a significant effect on Customer Loyalty, Menu Diversity has a significant effect on Customer Loyalty, Servicescape through Customer Satisfaction has a significant effect on Customer Loyalty, Menu Diversity through Customer Satisfaction has a significant effect on Customer Loyalty.